Problem Based Learning Berbantuan Teknologi Google Classroom: Upaya Peningkatan Literasi Sains Siswa - Layly Sailatus Sa'adah; Try Hartiningsih; Mochammad Ahied; Dwi Bagus Rendy; Siti Eneng Sururiyatul Mu’aziyah (PT. Komunitas Peneliti Alinea, 2025)
This study aims to determine the improvement in students' scientific literacy skills after the implementation of the Problem Based Learning model assisted by Google Classroom technology. The type of research used is experimental research (pre-experimental using a one-group pretest-posttest design) with a quantitative approach and using a nonprobability sampling technique with a purposive sampling design conducted at the UPTD SMPN 1 Arosbaya in the 2024/2025 academic year. The population used was all students of grade VIII, while the sample used was class VIII-C. The data collection technique employed a scientific literacy test, and the data analysis technique used the N-Gain Score test. The results of the study showed that: there was an increase in students' scientific literacy skills based on the N-Gain Score of 0.66 with a moderate category. Based on these results, it is recommended that future researchers pay more attention to time management during the implementation of the Problem Based Learning model assisted by Google Classroom technology, as this learning model requires a longer duration to complete each stage effectively.